Protective Microglia and Their Regulation in Parkinson’s Disease - Le, Weidong; Wu, Junjiao; Tang, Yu (Frontiers in Molecular Neuroscience, 2016)
Microglia mediated neuroinflammation is a hallmark of Parkinson’s disease (PD). It has been reported that microglia in the brain of PD have both neurotoxic and neuroprotective effects, depending on the microglial activation states. In this review, we will focus on the recent research findings of the neuroprotective role of microglia-mediated neuroinflammation in PD. Accumulating new evidences have indicated that the protective mechanisms of microglia may result from its regulation of transrepression pathways via nuclear receptors, anti-inflammatory responses, neuron-microglia crosstalk, histone modification and microRNA regulation. All of these protective mechanisms of microglia orchestrate with each other to repress the production of neurotoxic inflammatory components. Since the detrimental effects of inﬂammation overwhelm the protective effects of microglia during the disease progression of PD, exploring an in-depth understanding of the protective mechanisms of microglia and promoting the transformation of beneficial microglia are urgently important for the treatment of PD.